Pengembangan Model Asesmen Autentik Berbasis Karakter Santri Sebagai Upaya Penyiapan Generasi Unggul dan Berdaya Saing - Rizkiwati, Baiq Yuliana; Farid, Lalu Fathul (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2017)
The purpose of this research and development are: 1) to produce syllabus base on santri characters, 2) Produce an authentic santri based guidance books in the subject of Ethics and Profession Education as an effort to prepare superior and competitive generation.3) To know the validity of the authenticity assessment model based on the character of santri as an effort to prepare superior and competitive generation that has been developed according to the assessment of content / assessment experts, linguists and design experts. 4) To know the effectiveness of the authentic assessment model based on the character of santri through the responses of students and lecturers towards the application of authentic assessment models based on the character of santri. This type of research is a research development with Borg and Gall model that has been modified into eight development steps. Development steps include: 1) preliminary research, 2) planning, 3) product development, 5) design validation, 5) design revisions, 6) product trials, 7) product revisions, and 8) final product. Data collection techniques used are authentic assessment documents based on santri characters developed, observation and questionnaire applied in the form of research instruments. Data analysis techniques used descriptive qualitative analysis techniques and descriptive statistics.     The result of the research shows that the authentic assessment model based on the character of santri is very feasible to be used, it is proved by the assessment scores of 80.00% (quite reasonable), the linguist is 82.9% (reasonable enough), and the design expert is 86.7% (feasible). The developed product is tested to try on 20 students of the fourth semester who are taking the course of Ethics and Profession of Education in the study program of economic education of hamzanwadi University academic year 2016/2017 to know its effectiveness through student characteristic observation before and after the implementation of the assessment using santri character based assessment model that the difference between the results before and after, obtained the average percentage before the amount of 56.00% with the category of santri characters "began to grow". Average Percentage after obtained percentage of 75.00% with the character of santri "Culture". while the results of student responses with average percentage of 87.1% with the category worth to use, and obtained the average value of lecturer's response percentage of 88.00% with the category "decent". It proves that the use of authentic assessment model based on santri character is effective in assessing student santri character